Peran Pendidikan Agama Islam Berbasis Rekonstruksionisme dalam Membentuk Generasi yang Berakhlak dan Adaptif - Dela Andriani; Putri Nurhidayah; Herlini Puspika Sari (Dialektika : Jurnal Pendidikan Agama Islam, 2025)
Conventional Islamic Religious Education (PAI), with its strong emphasis on normative and ritual aspects, often struggles to address contemporary social challenges and global transformation, resulting in a gap between religious values and social engagement (Nata, 2014; Muhaimin, 2004). This study aims to conceptually examine and develop a theoretical model of Reconstructionism-based PAI that connects Islamic ethical principles with social action. Using a Library Research method supported by Concept Analysis and Theory Synthesis, the study analyzes primary works of Reconstructionist philosophy (Brameld, 1956) and literature on transformative PAI through Content Analysis and Comparative–Synthesis techniques, with data credibility strengthened through Source Triangulation (Lincoln & Guba, 1985). The theoretical synthesis indicates that integrating Reconstructionism offers a coherent framework for restructuring PAI toward issue-centered learning, critical inquiry, and socially oriented action. This model conceptually supports the development of Transformative Ethics (Gusau, 2021) and adaptive socio-religious skills, positioning PAI as a more responsive and action-oriented educational approach. The novelty of this study lies in formulating a philosophical model that aligns Islamic values with Reconstructionist principles, providing a conceptual basis for future empirical development and curriculum reform. Keywords: Islamic Religious Education, Reconstructionism, Transformative Ethics, Social Action.